Epidemiological profileof patientswith human immunodeficiency Virus (HIV) coinfected with hepatitis c Virus (HCV) inthe clinicof DST/aids cityof criciúma - Calegari, Camila B; Oenning, Roberto T; Spillere, Andréa C; Trento, Maria Joanna B; Fuzina, Deborah G (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: HIV/HCV coinfection represents a public health issue, complicating the treatment of both HIV and hepatitis C through increased hepatotoxicity. By sharing similar route of transmission coinfection of HCV in HIV positive patients is often found. Objective:to know the epidemiological profile of patients with HIV who are coinfected with hepatitis C virus in the clinic of STD/aids in the city of Criciúma, SC. Methods: this documentary is a retrospective, descriptive and exploratory study that evaluated charts of 97 patients who attended in the STD/aids clinic in Cricíuma from jan/2007 to dec/2009. Results: from a sample of 97 files reviewed, 25% of patients were female and 75% male. The average age among women was: 43.29 ± 9.888 SD and men: 42.61 ± 23.364 SD. As for the sexual situation 74% were heterosexual, homosexual 9%, 8% ignored, 6% bisexual, 3% were sex workers. In relation to risk 30% were intravenous drug users, hemophiliacs 2% and 68% ignored. Regarding sexual practices, 65% had multiple partners, 16% steady partner, 15% ignored, 3% partner with HIV/aids, 1% partner with multiple partners and HIV/aids. Conclusion: coinfection HIV/HCV occurs more frequently in males, since these patients are more susceptible than women to risk factors. The route of sexual transmission may have some importance in the transmission of HCV, at least in this study. However, subsequent studies that can confirm this hypothesis with the current study are needed.